ChatGPT and the Reconfiguration of Religious Authority: An Islamic Epistemological Perspective on Artificial Intelligence in Education - Salsabila Mustopa; Hasan Basri; Andewi Suhartini (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2026)
The proliferation of artificial intelligence has significantly reshaped the landscape of religious knowledge production and authority in contemporary Islamic contexts. This study investigates how ChatGPT, as an emergent digital agent in religious discourse, can be epistemologically situated within classical Islamic frameworks. Employing a Systematic Literature Review (SLR) guided by PRISMA protocol and thematic analysis, this research pursues three objectives: (1) to philosophically characterize knowledge produced by ChatGPT; (2) to locate ChatGPT within the bayani burhani irfani epistemological framework; and (3) to propose a conceptual model of reconstructed religious authority responsive to digital religion, religious moderation, and Islamic Religious Education (PAI). The analysis establishes that ChatGPT's outputs are fundamentally derivative, probabilistic, and devoid of value commitment, placing it most appropriately within the burhani domain as an informational instrument requiring scholarly curation. A four-layer hierarchical model is proposed anchored in revelation and maqasid al-shari'ah at the apex, followed by ulama as curators, scientific methodology as burhani instrument, and AI as technical support. This study's novelty lies in the systematic integration of Islamic epistemology with digital religion theory to reconfigure religious authority in the AI era and advance religiously moderate PAI.